The Effectiveness of the Self-Protection Model on Children’s Assertive Behavior In Sexual Violence - Amnestito, Zafhira Alayda; Jati, Sri Nugroho; Vidyastuti (Utan Kayu Publishing, 2024)
Children are particularly vulnerable to sexual violence because they are considered weak or powerless. Research data has found that 20% to 33% of girls and 10% to 16% of boys will become victims of sexual abuse before the age of 18. Kubu Raya Regency recorded that in 2021, there were 74 cases of violence against children and adolescents, which is quite high, with the majority of cases being sexual violence experienced by children aged 6-12 years. This indicates that children need to learn self-protection efforts through the Self-Protection Model. The Self-Protection Model is an intervention model provided as an effort to address the issue of sexual violence against children. This study employs a quantitative experimental design. The study uses purposive sampling, targeting children aged 9-12 years; attending elementary school; and willing and permitted by the school to participate until the intervention sessions are completed, with a total of 10 boys and 10 girls. Data analysis shows a difference in the application of the Self-Protection Model. The results of the Wilcoxon test output